2007
DOI: 10.4049/jimmunol.178.11.7467
|View full text |Cite
|
Sign up to set email alerts
|

Comparing ELISA and Surface Plasmon Resonance for Assessing Clinical Immunogenicity of Panitumumab

Abstract: Evaluation of the immunogenicity of panitumumab, a fully human anti-epidermal growth factor receptor mAb approved for use in colorectal cancer patients, led to the development of two separate immunoassays for the detection of anti-panitumumab Abs. The first immunoassay used a bridging ELISA capable of detecting 10 ng/ml positive control anti-panitumumab Ab. The ELISA incorporated an acid dissociation step to reduce drug interference and tolerated the presence of ∼100-fold molar excess of drug. During eight cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
86
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(94 citation statements)
references
References 10 publications
8
86
0
Order By: Relevance
“…This finding warranted a side-by-side comparison of both techniques to assess the possibility of identifying false positive/false negative HAHA responders. Such approach was taken by Lofgren et al [27] and indeed they identified more HAHA positives samples when applying SPR technology.…”
Section: Ab3 Inductionmentioning
confidence: 99%
“…This finding warranted a side-by-side comparison of both techniques to assess the possibility of identifying false positive/false negative HAHA responders. Such approach was taken by Lofgren et al [27] and indeed they identified more HAHA positives samples when applying SPR technology.…”
Section: Ab3 Inductionmentioning
confidence: 99%
“…Assay control data were generated by three validated semiquantitative immunogenicity immunoassays each using a different previously described detection technology-electrochemiluminescence (ECL) (8), ELISA (9), and surface plasmon resonance (SPR) (10). Each immunogenicity immunoassay was used in the routine analysis of clinical samples.…”
Section: Semiquantitative Immunogenicity Immunoassay Methodsmentioning
confidence: 99%
“…Enzyme-linked immunosorbent assays (ELISA) and electrochemiluminescence (ECL) immunoassays [7] are among the most widely used platform for ADA detection. Other platforms that have been used include surface plasmon resonance and bio-layer interferometry which may be more suited for detection of low affinity ADA [8]. Typically, detection of ADA is followed by assessments of the magnitude (titer) of the ADA response and the in vitro neutralizing ability of ADA, especially in late-stage clinical studies.…”
Section: Introductionmentioning
confidence: 99%